The Effect Of Giving Active Cycle Of Therapy Breathing Technique (ACBT) On Respiratory Rate In Pulmonary Tuberculosis Patients At Arifin Achmad Hospital Riau Province - Defi Eka Kartika; Sandra; Yolanda , Martha (Infomasi dan Promosi Kesehatan, 2025)
Pulmonary tuberculosis is a major public health problem in the world and is the second cause of death from infectious diseases. The main complaints experienced by pulmonary TB sufferers include coughing for more than 3 weeks, coughing up phlegm, coughing up blood, chest pain, fever, night sweats, malaise, decreased appetite, decreased weight, shortness of breath, and accumulation of secretions that are difficult to expel. The consequences of not expelling sputum smoothly cause the airway to become ineffective so that sufferers experience difficulty breathing. Efforts that can be given to pulmonary TB sufferers to overcome ineffective airway clearance are by doing breathing exercises. Breathing exercises are a nursing action in the management of patients with respiratory system problems. Breathing exercises that can be done by pulmonary TB sufferers are Active Cycle Of Breathing Technique. The aim of this research is to determine the effect of giving active cycle of breathing technique (ACBT) therapy on improving breathing patterns in pulmonary tuberculosis sufferers. The research method used is a quantitative type of research, with the research design used being a pre-experimental approach with a one group pre test and post test research design. The location of this research was carried out in the Jasmin room at Arifin Achmad Hospital, Riau Province and the time this research began was July - August 2024. The sample technique for this research was random sampling. The number of samples in the study was 17 people. There is an effect of giving active cycle of breathing technique (ACBT) therapy on improving breathing patterns in pulmonary tuberculosis sufferers with p=0.00.